The Influence of Profitability and Capital Structure on Stock Returns (Study of Retail Companies Listed on the Indonesia Stock Exchange for the Period 2020 – 2024) - Evi Puspita Sari; Anwar; Andi Mustika Amin; Nurman; Abdul Rahman (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study analyzes the effect of profitability (measured by Return on Equity, ROE) and capital structure (measured by Debt to Equity Ratio, DER) on stock returns in 10 retail sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The background of the study is based on fluctuations in stock returns in the retail sector, which are influenced by internal factors such as profitability and capital structure, as well as theories such as Signaling Theory and Trade-Off Theory. The main objective is to test whether these two independent variables significantly affect stock returns. The method used is multiple linear regression with secondary data analysis through SPSS 27, after conducting classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The results show that capital structure (DER) has a positive and significant effect on stock returns, supporting the Trade-Off Theory, while profitability (ROE) has no significant effect, which contradicts the Signaling Theory. Simultaneously, both variables have a significant effect on stock returns. This conclusion suggests that retail companies should focus more on optimizing capital structure to increase stock returns. The implications of this research provide empirical contributions for investors and company management in facing economic uncertainty..